Study on the correlation between IL-12p70, IL-17A and migraine in children - Yang, Fan; Liu, Hai-zhen; Liu, Jia-ai; Chen, Yao-yao; Sun, Su-zhen (Frontiers in Neurology, 2024)
Objective To compare the serum levels of 12 cytokines in migraine group, encephalitis with headache symptoms group, pneumonia without headache symptoms group and migraine subgroups to explore the cytokines associated with migraine in children and their levels. Methods A total of 44 children with migraine, 27 children in the encephalitis group with headache symptoms and 44 children in the pneumonia group without headache symptoms were selected from January 2022 to August 2023 in Hebei Children’s Hospital. They were all tested for serum cytokines by immunofluorescence assay. The migraine group was further divided into subgroups according to different age, gender, course of disease, and presence of coinfection. The differences of serum cytokine levels among the above groups were compared, and the correlation analysis was carried out. Results Except IL-5, there were no significant differences in the expression levels of other 11 inflammatory cytokines between migraine subgroups. Compared with encephalitis with headache symptoms group and pneumonia without headache symptoms group the serum levels of IL-4, TNF-α, IL-17A, and IL-12p70 were higher in migraine group than in pneumonia group, and the levels of IL-12p70 were higher than those in encephalitis group (p < 0.05). An increase in serum IL-12p70 (OR = 1.267, 95%CI 1.054–1.523, p = 0.012) and IL-17A (OR = 1.066, 95%CI 1.016–1.119, p = 0.010) levels had a significant effect on migraine. Conclusion Elevated serum levels of IL-12p70 and IL-17A may increase the risk of migraine in children, which has certain diagnostic and predictive value.